Efektifitas Lotion Anti Nyamuk Ekstrak Etanol Daun Kenikir (Cosmos caudatus) - Suprianto Suprianto; Hendri Faisal; Endang Subekti (Journal of Indah Science and Clinic, 2021)
Mosquitoes are one of the insects whose presence is often disturbing. Plants of Kenikir (Cosmos caudatus) contains saponins, polyphenols, and volatile oils. This study uses an experimental method. Tests carried out include: organoleptic, homogeneity, pH, and effectiveness. The results showed that Kenikir leaf extract has effectiveness in resisting mosquitoes. Organoleptic test of lotion with a concentration of 5%, 10%, and 15% have a dark green colour and has a distinctive odour of Kenikir. Homogeneity test of lotion with a concentration of 5% is homogeneous, while concentrations of 10% and 15% are not homogeneous. Homogeneity and organoleptic tests have fulfilled the requirements of mosquitoes repellent lotion. The resulting lotion effectively repels mosquitoes